Komunikacja międzynarodowa i międzykulturowa w przedsiębiorstwie - Stor, Marzena (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
International communication in a company attracts more and more interest among practitioners and academic theorists who are engaged in management. The reason is more companies go international and they need to know how to communicate with people from different cultures. The main goal that the author of this article wants to achieve is to outline the importance of interpersonal relations for enhancing business competitiveness. The issue to be discussed is very specific as it concerns multinationals and their socially diverse stakeholders. In this kind of organizations interpersonal relations are determined by intercultural communication which in turn may condition development of international communication. And, what is worth emphasizing, international communication itself is of a very special significance since it is associated with company's goal achievement and strategy realization. Three virtual problems are analyzed then: 1) interrelations between international communication and cross-cultural communication, 2) intercultural communication in diversity management as competitiveness-oriented policy, 3) communication conditions that foster increase in effectiveness that international management teams are supposed to reach. The final conclusion is there are some features that should characterize communicating parties whose intention is to succeed in communication both international and intercultural. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Nauki Humanistyczne (10); 2006; nr 1149, s. 276-288